2019
DOI: 10.1108/jabs-03-2019-0086
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of online purchase intention: a PLS-SEM approach: evidence from Indonesia

Abstract: Purpose The purpose of this paper is to identify the factors affecting consumers' online purchase intention and to explore whether there was any significant difference between the path coefficients for males and females. Design/methodology/approach Data were collected by distributing questionnaires to 668 Indonesian consumers who were actively using the internet. The data were analyzed using partial least squares structural equation modeling (PLS-SEM) and multi-group analysis (MGA) in SmartPLS 3.0 software. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 71 publications
8
58
0
4
Order By: Relevance
“…My research support to other finding that the most important reason for the rise of e-commerce is a more reasonable price [22]. Other finding revealed that consumers will purchase using online channels if it will be profitable, efficient, effective and productive [23].…”
Section: Category Of Subjective Normssupporting
confidence: 78%
“…My research support to other finding that the most important reason for the rise of e-commerce is a more reasonable price [22]. Other finding revealed that consumers will purchase using online channels if it will be profitable, efficient, effective and productive [23].…”
Section: Category Of Subjective Normssupporting
confidence: 78%
“…Consumer trust, perceived value, buying predisposition, and satisfaction are instrumental in articulating behaviors, attitudes, and intentions to adopt mobile shopping (Anshari et al, 2021;Dewi et al, 2020;Ghazali et al, 2018;Liu et al, 2020;Sharma et al, 2018;Tarhini et al, 2019), constituting motivational factors in purchasing products and services (Cho & Son, 2019;Graf-Vlachy et al, 2018;Loh et al, 2021;Roy et al, 2020;Seeger et al, 2019;Touzani et al, 2018). Consumer use behavior in relation to mobile payment services and apps (Bhattacharya & Anand, 2019;Kaur et al, 2020;Rodríguez-Torrico et al, 2020) is configured by consumer perceived value and motivation, online convenience, continuance intention, and impulse buying behavior Kim et al, 2021;Patel et al, 2020).…”
Section: Theoretical Overview Of the Main Conceptsmentioning
confidence: 99%
“…The fashionableness of online social networks has influenced the shopping decisions of mobile shopping apps users (Bhattacharya & Anand, 2019;Dewi et al, 2020;Li & Ku, 2018;Phong et al, 2018) on social commerce sites. The main conclusions of these studies indicate that the push effect, as regards low transaction efficiency, discourages consumers from using e-commerce sites.…”
Section: Consumer Motivational Factors In Purchasing Products and Services By Use Of Mobile Shopping Appsmentioning
confidence: 99%
“…In this study, personal innovation represents the personal characteristics of the farmers in terms of actively exploring new and unknown things and the stronger personal innovation of farmers, the higher degree of initiative in exploring new things, which implies the stronger initiative in understanding and adopting IoT traceability technology. Dewi et al [24] proposed that personal innovation had a crucial role in innovation adoption and also had a strong and direct effect on consumers' decision to adopt new technology because individuals became aware of new technology based on personal traits such as personal innovation. It can be concluded that the more innovative the consumers are, the higher the behavioral intention will be.…”
Section: Hypothesis 3 (H3) Social Influence Has a Positive Impact On Farmers' Adoption Willingness Of Iot Traceability Technologymentioning
confidence: 99%